A Critical Approach to Integrating Christian Disability Theology in Clinical Rehabilitation - Barton, Sarah Jean (Journal of disability & religion, 2017)
The integration of disability studies into clinical rehabilitation is a minimally explored area. Based on current literature, the field of disability studies alone provides insufficient resources for the formation of renewed clinical practices. The use of theological perspectives on disability facilitates creation of clinical practices within a disability studies framework. Theological voices enhance participation and flourishing for all persons involved in rehabilitation. Drawing primarily from Nancy Eiesland's The Disabled God, the author argues that seriously engaging theology creates space to counter medicalized and violent practices of rehabilitation and allows unity, embodied solidarity, and resymbolization to flourish within the clinic.